Impacts of Large‐Scale Sahara Solar Farms on Global Climate and Vegetation Cover - Zhengyao Lu; Qiong Zhang; Paul A. Miller; Qiang Zhang; Ellen Berntell; Benjamin Smith (Geophysical Research Letters)
Abstract Large‐scale photovoltaic solar farms envisioned over the Sahara desert can meet the world's energy demand while increasing regional rainfall and vegetation cover. However, adverse remote effects resulting from atmospheric teleconnections could offset such regional benefits. We use state‐of‐the‐art Earth‐system model simulations to evaluate the global impacts of Sahara solar farms. Our results indicate a redistribution of precipitation causing Amazon droughts and forest degradation, and global surface temperature rise and sea‐ice loss, particularly over the Arctic due to increased polarward heat transport, and northward expansion of deciduous forests in the Northern Hemisphere. We also identify reduced El Niño‐Southern Oscillation and Atlantic Niño variability and enhanced tropical cyclone activity. Comparison to proxy inferences for a wetter and greener Sahara ∼6,000 years ago appears to substantiate these results. Understanding these responses within the Earth system provides insights into the site selection concerning any massive deployment of solar energy in the world's deserts.